THE DURATION OF PLANTING, THE NORM AND THE EFFECT OF THE NORMS OF ORE FERTILIZERS ON THE PROTEIN CONTENT OF THE GRAIN OF AUTUMN RYE VARIETIES - B. R. Xasanov (Web of Journals Publishing, 2024)
This article studied and analyzed the effect of planting winter rye varieties "NS Savo" and "Vakhshskaya 116" as well as fertilizing with different rates of fertilizers on the amount of protein in the conditions of light gray soils of the Kashkadarya region.
Keywords: rye, variety, sowing time, sowing rate, mineral fertilizer rate, protein content, “Ns Savo” and “Vakhshskaya 116”.